Stressed-deformed state of two drifts in a tiltly layered cracked array in the conditions of elastic deformations of rocks - Azhikhanov, N. T.; Zhumagulov, B. T.; Turymbetov, T. A.; Bekbolatov, A. B. (Journal of Mathematics, Mechanics and Computer Science, 2020)
In the study, based on a homogeneous anisotropic mechanical-mathematical mo del of an inclined, finely layered array with a bip erio dic system of slots, the patterns of distribution of elastic stresses and displacements near two drifts of arbitrary profile shap e and depth by the finite element metho d under conditions of plane deformation have b een systematically numerically investigated. The calculation was carried out by converting weakened ro cks with two excavations in elasticity to an equivalent homogeneous medium. It is difficult to solve the problem of the initial static stress state of two-diagonal workings on a ro ck weakened by two-p erio d cracks by the analogous metho d, therefore it was solved by the generalized metho d of plane deformation using the first and second isoparametric elements by the finite element metho d. Metho ds for dividing the area sp ecified by the finite element metho d into parametric quadrangular elements and numerically determining the stress-strain state of double workings are given. A computational algorithm has b een develop ed and a software package has b een develop ed for studying the elastic state of adjacent cavities of arbitrary depth and shap e. A multivariate numerical calculation and analysis of the influence on the comp onents of stresses and displacements near cavities, geometrical, physical parameters of ro cks was carried out.